The Policy of European Communities in the Sphere of Higher Education in the 1950s and 1960s: Ideas and Their Implementation - Leskina, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2018)
This paper analyses one of the most under-researched stages of European Communities’ policies, including the European Coal and Steel Community (ECSC), the European Economic Community (EEC) and European Atomic Energy Community, in the sphere of higher education between the 1950s and 1960s, because it is characterised by a very intense search for ideas and the most active resistance to their implementation. The dominating economic explanation of the shift to supranational regulation in the 1970s existing in research works available seems insufficient, because it does not provide reasons why it occurred during the era of Euroscepticism, i.e. a setback in European integration. The aim of the paper is to analyse the evolution of educational cooperation during this period using transactional approach, involving the development of supranational regulation with transnational activities. The research relies on the official documents of Euratom and EEC, speeches of politicians on the “European dimension” of higher education, as well as documents reflecting positions of universities. Referring to their analysis, the author concludes that the discussion of the possible ways of harmonisation of higher education in Europe and Community policy making in this field had started well before its stipulation in official documents in the 1970s. This prolonged process was characterised by the search for new ideas and their adjustment to the environment of the period in question. Relying on the transnational community and networks, simultaneously fostering their development, supranational bodies garnered support for their activities. The cooperation between European Communities and academia allowed for the laying of foundations of a new supranational European dimension in universities.